Socrates, Problem-based Learning and Critical Thinking—A Philosophic Point of View - Shin-Yun Wang; Jer-Chia Tsai; Horn-Che Chiang; Chung-Sheng Lai; Hui-Ju Lin (Kaohsiung Journal of Medical Sciences, 2008)
Problem-based learning (PBL) is a learner-centered educational method based on the principles of heuristics and collaboration. It has been considered an effective learning method in general and in professional education, especially in medical education. This article analyzes the thinking structure and philosophical background of PBL through the educational ideas of Socrates and the truth conception of Karl Popper. In the different phases of the PBL process, various truth conceptions will help to formulate the thinking framework of PBL—from Socrates' truth of openness toward the truth of scientific accuracy of our modern age. Meanwhile, Popper's scientific theory of falsifiability further leads us to discuss the relationship between PBL and critical thinking.